Rozważania wstępne dotyczące czynników inicjujących i hamujących proces społecznej amnezji o akcji „T4” - Kopeć , Danuta (Studia Edukacyjne, 2024)
The text offers preliminary considerations of the factors initiating and inhibiting the process of social amnesia about Operation T4. Carried out by the Nazis, this operation was designed to exterminate those whose lives were described as “unworthy of life/Lebensunwertes Leben”. This group included both adults and children, primarily persons in a mental health crisis and with disabilities. Figures from the year 2000 show that about 216,400 people were killed in Germany and Austria, 80,000 in the occupied territories, and 20,000 in the lands of the Second Polish Republic. It is striking that there is social amnesia about Operation T4 in Germany, Austria, and Poland. There is no doubt that disrupting the process of social amnesia is vital for the commemoration of the victims of Operation T4. To do so, it is crucial to know the initiating and inhibiting factors behind this amnesia. The text attempts to describe them in the context of two perspectives: individual and collective. The factors initiating and inhibiting the process of social amnesia about Operation T4 in the collective perspective have been analyzed in the context of three time periods: 1) the inter-war and wartime period up to 1945; 2) the post-war period, from 1945 until the end of the 1980s; 3) contemporary period, from early 1990s.